2013
DOI: 10.1128/aem.00202-13
|View full text |Cite
|
Sign up to set email alerts
|

New Group in the Leptospirillum Clade: Cultivation-Independent Community Genomics, Proteomics, and Transcriptomics of the New Species “Leptospirillum Group IV UBA BS”

Abstract: Leptospirillum spp. are widespread members of acidophilic microbial communities that catalyze ferrous iron oxidation, thereby increasing sulfide mineral dissolution rates. These bacteria play important roles in environmental acidification and are harnessed for bioleaching-based metal recovery. Known members of the Leptospirillum clade of the Nitrospira phylum are Leptospirillum ferrooxidans (group I), Leptospirillum ferriphilum and "Leptospirillum rubarum" (group II), and Leptospirillum ferrodiazotrophum (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 54 publications
2
38
0
Order By: Relevance
“…Genes for the respiratory [NiFe]‐hydrogenase ( hydAB ), a [NiFe]‐hydrogenase large subunit ( hoxH ), and the hydrogenase maturation protein were found in Leptospirillum group IV (Goltsman et al ., ). However, previous results revealed that strains belonging to L. ferriphilum and L. ferrodiazotrophum did not grow on hydrogen, indicating that ferrous iron was used as the sole electron donor in these acidophiles (Hedrich and Johnson, ).…”
Section: Metabolic Diversity Of Iron‐ And/or Sulfur‐oxidizing Autotromentioning
confidence: 97%
See 3 more Smart Citations
“…Genes for the respiratory [NiFe]‐hydrogenase ( hydAB ), a [NiFe]‐hydrogenase large subunit ( hoxH ), and the hydrogenase maturation protein were found in Leptospirillum group IV (Goltsman et al ., ). However, previous results revealed that strains belonging to L. ferriphilum and L. ferrodiazotrophum did not grow on hydrogen, indicating that ferrous iron was used as the sole electron donor in these acidophiles (Hedrich and Johnson, ).…”
Section: Metabolic Diversity Of Iron‐ And/or Sulfur‐oxidizing Autotromentioning
confidence: 97%
“…Genomic analyses revealed that A. ferrooxidans, A. ferrivorans, and members of groups I, III, and IV of the Leptospirillum genus harbor several genes encoding the nitrogenase complex (Table 2) (Levic an et al, 2008;Goltsman et al, 2013). However, A. thiooxidans and A. caldus, both of which lack genes encoding the nitrogenase complex, carry genes associated with the Fig.…”
Section: Nitrogen Assimilationmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, many acidophile studies have utilized “omics” techniques, including proteomics to investigate not only whole communities (Belnap et al, 2011; Mueller et al, 2011; Goltsman et al, 2013) but also specific responses in a single species (Baker-Austin et al, 2010; Mykytczuk et al, 2011; Potrykus et al, 2011; Mangold et al, 2013). In this study, iron oxidation and biomining studies along with a proteomic strategy are used to investigate the differing responses to chloride by the salt susceptible and tolerant acidophiles At.…”
Section: Introductionmentioning
confidence: 99%